Research on the Construction and Prediction of China's National Fitness Development Index System Under Social Reform - Liu, Zheng; Zhang, Shijia; Li, Lingling; Hu, Bin; Liu, Ran; Zhao, Zhao; Zhao, Yuanjun (Frontiers in Public Health, 2022)
Background National fitness is a development plan formulated by China to promote people's participation in leisure and fitness, enhance people's physique, and realize the general goal of strengthening sports. Methods Based on combing the development process of China's national fitness after reform and opening up, using the improved “balanced scorecard” method, this article constructs an evaluation index system of the national fitness development index. Results The national fitness development index was established, including 4 first-level indicators, 14 second-level indicators, and 49 third-level indicators. It can calculate the national fitness development index with a total score of 100 points. Conclusion To verify the feasibility of the evaluation system, the goal current situation evaluation method is used to calculate the national fitness development index during the 14th Five Year Plan period based on the development of national fitness during the 13th Five Year Plan period to provide evaluation tools and theoretical reference for the development of national fitness in China.